Improving the Efficiency of Cutting Tools through Application of Filtered Cathodic Vacuum Arc Deposition Coating Techniques: A Review - Hailu Gemechu Benti; Abraham Debebe Woldeyohannes; Belete Sirahbizu Yigezu (Advances in Materials Science and Engineering)
The challenge of enhancing cutting tool life has been dealt with by many research studies. However, this challenge seems endless with growing technological advancement which brings about incremental improvement in tool life. The objective of this review paper is focused at assessing filtered cathodic vacuum arc deposition techniques applied on cutting tools and their effect on tool efficiency. The paper particularly picks filtered cathodic vacuum arc deposition (FCVAD) among other well-identified methods of coating like the Chemical Vapor Deposition (CVD) and Physical Vapor Deposition (PVD). Filtered Cathodic Vacuum Arc Deposition is the state of art in the coating technology finding wide application in the electronics industry and medical industry in addition to the machining industry, which is the concern of this review paper. This review is made in order to summarize and present the various techniques of FCVAD coatings and their applications, as investigated by various researches in the area.